2012
DOI: 10.1161/circgenetics.111.962415
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Computational and Experimental Analysis of the Neuroendocrine Transcriptome in Genetic Hypertension Identifies Novel Control Points for the Cardiometabolic Syndrome

Abstract: Background Methods and Results We developed a novel, integrative method (combining animal models, transcriptomics, bioinformatics, molecular biology, and trait-extreme phenotypes) to identify candidate genes for essential hypertension and the metabolic syndrome. We first undertook transcriptome profiling on adrenal glands from blood pressure extreme mouse strains: the hypertensive BPH and hypotensive BPL. Microarray data clustering revealed a striking pattern of global underexpression of intermediary metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Further analysis of human population indicated that a single nucleotide polymorphism of Yy1 was associated with BP, body mass index, and fasting glucose. They suggested this gene as the strongest candidate influencing hypertension and metabolic syndrome (Friese et al, 2012).…”
Section: Molecular Contributions To Hypertension In Bph/2 Micementioning
confidence: 99%
“…Further analysis of human population indicated that a single nucleotide polymorphism of Yy1 was associated with BP, body mass index, and fasting glucose. They suggested this gene as the strongest candidate influencing hypertension and metabolic syndrome (Friese et al, 2012).…”
Section: Molecular Contributions To Hypertension In Bph/2 Micementioning
confidence: 99%
“…Different animal models of arterial hypertension help to analyze the transcriptome of the adrenal glands and to uncover common genetic mechanisms of hypertension across mammalian species that might, therefore, be pertinent to human hypertension too [3, 4, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to potential repair of the “wet beri-beri” lesions noted above, analyses of the transcriptome in rodent genetic models of hypertension reveal widespread changes in mRNAs encoding components of carbohydrate intermediary metabolism (5153), including the thiamine-dependent transketolase step in the pentose phosphate pathway.…”
Section: Discussionmentioning
confidence: 99%